Personality profile of the satisfied and dissatisfied Greek university students - Anderson, Lynn R. (The Greek Review of Social Research, 1975)
From a large sample of Greek university students (N — 1200) those students who were highly satisfied and those students who were highly dissatisfied with their educational program were selected by means of a semantic differential x attitude test. The satisfied group consisted of 99 males and 92 females while the dissatisfied group consisted of 36 males and 20 females. Mean scores on a Greek translation of the Edwards Personal Preference Schedule were computed for these four groups of students. The results indicate that satisfied males are significantly higher than dissatisfied males on need for order and significantly lower than dissatisfied males on need for autonomy. Satisfied females are signifi cantly higher than dissatisfied females on needs for order and affiliation and significantly lower than dissatisfied females on needs for dominance and autonomy. The variable of need for achievement did not differ between satisfied and dissatisfied groups for either sex. The results suggest that satisfied students, regardless of sex, tend to be conforming, passive and (for females) interpersonally oriented. Dissatisfied students tend to be independent, non-conforming, and (for females) dominating. The two groups (satisfied vs. dissatisfied) do not, however, differ in their needs for achievement and success. Both groups have «average » scores on this achievement variable—a fact which suggests that high achievement students are only moderately satisfied with their educational program. The research also presents further evidence for the validity and utility of the new Greek translation of the EPPS. Although this study is extracted from the same data that were used for the standardization of the Greek EPPS, the data do support an intuitively sensible interpretation of the personalities of satisfied and dissatisfied university students. Further research using the Greek EPPS should be able to demonstrate the utility of the test as both a counseling and research instrument.